Environmental Estimation of Radiation Equivalent Dose Rates in Soils and Waters of Northern Calabria (Italy) - Ilaria Guagliardi; Tommaso Caloiero; Ernesto Infusino; Giovanni Callegari; Nicola Ricca (Geofluids)
In this study, the equivalent dose rate of natural radionuclides (HT) in 99 spring water and surface soil samples was determined using an alpha, beta, and gamma high sensitivity detector up within a Geiger-Muller tube and with an external probe NaI (Tl). The samples were collected in the Crati basin (southern Italy), and during sample collection, water quality parameters were detected in situ and at the University of Calabria laboratories. A Pearson correlation coefficient analysis was applied to identify and clarify the relationships between water physical-chemical properties and soil and water radioactivity. Results show that the mean HT for spring waters is 97.07 μSv/h. Furthermore, the mean HT for surface soils is 97.92 μSv/h, thus evidencing higher mean HT values than worldwide ones reported in a previous literature. Low correlation coefficients were detected between water HT and conductivity and pH. On the contrary, a reasonable correlation was found between HT in spring water and in soil. This relationship is associated with some rocks of the Sila Massif and of Coastal Chain, i.e., plutonic and metamorphic crystalline rocks. Finally, the estimation of the health risk was calculated: results did not evidence serious dangers for people living in the studied environment. The results from this survey for the HT evaluation provide an extensive assessment of the background exposure levels in the investigated area.